Persepsi Siswa SMP Negeri 35 Banjarmasin Terhadap Pernikahan Usia Dini - Permatasari, Rahmah; Puji Hastuti, Karunia; Muhaimin, Muhammad; Adyatma, Sidharta; Alviawati, Eva (geoedusains: Jurnal Pendidikan Geografi, 2024)
Early marriage in adolescents can have an impact on adolescent health, both physically and psychologically. The causes of early marriage are influenced by various factors, namely factors that arise within themselves and also from outside themselves. This research is entitled "Perceptions of Students of SMP Negeri 35 Banjarmasin Towards Early Marriage". This study aims to determine students' perceptions of early marriage. The population of this study were all ninth-grade students of SMP Negeri 35 Banjarmasin, totaling 118 students. The sample used as respondents is the entire population of 118. This research uses a quantitative descriptive method. Primary data collection techniques in this study used questionnaire techniques, while secondary data used document study techniques and literature studies. Data analysis in this study uses percentage techniques to determine the percentage of each question asked in the questionnaire. The results of this study indicate that the perceptions of students of SMP Negeri 35 Banjarmasin do not agree with early marriage.